Strategi Pembelajaran Berdiferensiasi Terhadap Hasil Belajar IPA Siswa: A Systematic Literature Review - I Gede Yudi Pratama; I Wayan Redhana; I Nyoman Tika (Jurnal Penelitian Pendidikan IPA, 2026)
In the independent curriculum, differentiated learning is known. Differentiated learning views students differently and dynamically. In this case, teachers view learning from various perspectives. However, this does not mean that differentiated learning is individualized learning. Differentiated learning is a learning approach that adapts learning to the needs of students starting from interests, learning styles, student readiness and other characteristics. In the process, differentiated learning consists of two types, namely differentiation based on learning styles and differentiation based on learning abilities. This study aims to explore differentiated learning related to the research design used, the right learning model, the effect of differentiated learning on students' science learning outcomes and the profile of the use of differentiated learning in science learning at various levels of education. This study is a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method. Publish or perish was used to collect data from Google Scholar with a span of 2021-2025, 1000 articles were identified and filtered based on criteria, resulting in 15 articles that met the criteria. Research on differentiated learning mostly uses Classroom Action Research (CAR) design. The learning model that is widely used is by combining differentiated learning strategies. Differentiated learning has a positive impact on student learning outcomes and activities. Differentiated learning can be applied at every level of education.